THE The Effect of Foot Massage and Warm Water Mixed with Aromatic Ginger Foot Bath on Edema in Pregnancy - Shinta Novelia; Rukmaini; Rista Veratu Caka (Nursing and Health Sciences Journal (NHSJ), 2022)
Swelling or edema in the legs often occurs in third trimester pregnant women because uterine pressure inhibits venous return causing fluid retention. The incidence of edema in RSIA Kemang Medical Care between December 2021 and January 2022 was third ranked in cases of discomfort for pregnant women. Handling swollen feet by means of complementary therapies, one of which is foot massage and warm water foot bath mixed with aromatic ginger.This quasi-experimental study used a two-group pretest and posttest design with control group. The population of this study was all registered pregnant women with third trimester edema which was 80 people. There are 20 experimental samples and 20 control samples. The sampling technique used purposive sampling. The instrument was SOP and pitting scale tables. Data analysis had been done by using Wilcoxon and Mann Whitney test. The average degree of leg edema was 3+ before the intervention and 1+ after the intervention. According to Wilcoxon, the results showed pvalue =0.000 (<0.05) so that statistically there was a significant decrease in leg edema before and after foot massage and footbath in warm water mixed with aromatic ginger in third trimester pregnant women. The Mann-Whitney test for the significant difference p = 0.000 < 0.05 there was a difference between the post- experimental group and the post control group, which means that statistically there was a decrease in swelling in the third trimester of RSIA Kemang Medical Care 2022 with foot massage